Development and testing of a pepper harvester - DEEPA K.P NISHANTH M. STANLY RAJEESH V.K; Dr. Jayan P.R (Guide) (Tavanur 2010 Kelappaji College of Agricultural Engineering and Technology)
Development and testing of a pepper harvester
Development and testing of a pepper harvester